IMPLEMENTASI TEORI ADMINISTRASI DALAM PENDIDIKAN STUDI KASUS DI SDN 4 DEPOK - Permana, Tatang; Supriatna, Acep; Dahtiar, Dadan; Nurmuminah, Ina; warta, Waska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of administrative theories in the management of education at SDN 4 Depok. The study responds to the challenges of applying educational administration practices in elementary schools that are often still traditional and formalistic, and have not fully adapted to modern administrative theories. Using a qualitative approach with a single case study method, the research explores planning, organizing, executing, and supervising activities in the school’s management, as well as supporting and inhibiting factors. The findings indicate that SDN 4 Depok has begun integrating modern administrative principles, such as participatory planning and initial use of technology, though the practices are still dominated by classical bureaucratic approaches with weaknesses in data-based evaluation, equitable task distribution, and systematic feedback. The study confirms that the school is in transition toward modern, collaborative, and data-oriented management. These findings are expected to contribute theoretically to the development of educational administration literature and practically as recommendations for improving the managerial capacity of elementary schools. Keywords: educational administration, classical theory, modern theory, school management, case study